Shear resistance of through-diaphragm connections between concrete-filled steel tubular column and H-shaped steel beam with tension field model. Issue 13 (October 2019) - Rong, Bin; Ma, Xu; Zhang, Ruoyu; Liu, Shuai
In this article, seismic behavior of through-diaphragm connections between concrete-filled steel tubular column and H-shaped steel beam was investigated through experimental and analytical studies. Three cruciform through-diaphragm connection specimens were tested under cyclic loading to investigate the shear behavior of panel zone. The studied parameters are infilled concrete strength and width-to-thickness ratio of the tube in the panel. The failure mode, load–displacement behaviour, ductility, and strength degradation of these specimens were analysed and discussed in detail. Based on the shear buckling of the panel zone observed in the test, the ultimate shear resistance of the tube web panel referring to the theory of tension field action was investigated. Finally, an analytical model was developed to predict the shear resistance of panel zone. The applicability of this model was validated by the test results.